Vascular normalization and immunotherapy: Spawning a virtuous cycle - Swamy, Kumara (Frontiers in Oncology, 2022)
Antiangiogenics, radiotherapy (especially stereotactic body radiotherapy - SBRT) /chemotherapy, and immunotherapy form a critical trimodal approach in modern-day cancer therapy. The normalization window, however short, forms the beachhead for the strategic initiation of decipherable disruption of the cancer cells. This opening can be the opportunity for designing controlled stepwise cancer cell death and immunological augmentation. The next step is to induce immunogenic cell death by chemotherapy/radiotherapy concurrently with the facilitation of professional phagocytosis. Immunotherapy at this stage, when interstitial pressure decreases considerably, leads to improved perfusion of oxygen with solutes, improved immune-friendly pH, and is additionally expected to open up the TME for a “flood” of tumor-infiltrating lymphocytes. Further, there would be enhanced interaction in “hot” nodules and incorporation of immune reaction in “cold” nodules. Simultaneously, added adjuvant-assisted neoantigen-immune cell interaction will likely set in a virtuous cycle of cancer cell death induction followed by tumor cell-specific antigenic reaction boosting cancer cell death, in turn improving the normalization of the vasculature, completing the loop. There should be a conscious concern to protect the extracellular matrix, which will nurture the long-term immunological cross-talk to discourage dormancy, which is as essential as getting a complete response in imaging. The evolution of immunotherapy to be a significant armamentarium and all the other parallel developments in the oncological field is of immense promise. The caveat is that available therapies should be appropriately ranked during the start of the treatment since the first time is the most opportune period. A fast-paced development in the field of nano- medicines is likely to be of assistance in all the steps enumerated.